2018
DOI: 10.1016/j.trd.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Policy effects on charging behaviour of electric vehicle owners and on purchase intentions of prospective owners: Natural and stated choice experiments

Abstract: Policy effects on charging behaviour of electric vehicle owners and on purchase intentions of prospective owners: Natural and stated choice experimentsWolbertus, Rick; Kroesen, Maarten; van den Hoed, Robert; Chorus, Caspar G. AbstractPolicy makers are looking for effective ways to promote the adoption of electric vehicles (EVs). Among the options is the roll-out and management of charging infrastructure to meet the EV drivers' refuelling needs. However, policies in this area do not only have a long-term effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 47 publications
(59 reference statements)
3
53
0
Order By: Relevance
“…Second, users predominantly charge where they already park. These assumptions are consistent with other research [30,31] and the anticipated user behavior for a mass-market of electric vehicles. For our case study, we use the 2008 German household travel survey (MiD) [23].…”
Section: Vector21supporting
confidence: 89%
See 1 more Smart Citation
“…Second, users predominantly charge where they already park. These assumptions are consistent with other research [30,31] and the anticipated user behavior for a mass-market of electric vehicles. For our case study, we use the 2008 German household travel survey (MiD) [23].…”
Section: Vector21supporting
confidence: 89%
“…We assume that electric vehicle users do not alter their travel patterns. This assumption is supported by the literature, but we are also limited by the lack of data on detailed travel information of electric vehicle users [30,31]. Second, electricity demand from BEVs is temperature and seasonally dependent, which was not considered in this model experiments but suggested e.g.…”
Section: Modelmentioning
confidence: 74%
“…The results of Mau et al [36] support the relevance of a range of vehicle attributes beyond the purchase price in shaping consumer preferences toward EVs. Wolbertus et al [37] showed that offering free parking has a positive effect on the purchase intention of EVs. Many drivers were concerned about the financial implications of purchasing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings from a national survey showed that recharging times have a considerable influence on consumers' preferences [21]. The effects of policies on charging behavior and EV adoption were studied in [59]. The authors used a large data set to investigate the influence of daytime and free parking policies on EV drivers' charging behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%